A New Phe-Free Protein Substitute Engineered to Allow a Physiological Absorption of Free Amino Acids for Phenylketonuria. (28th June 2018) - Giarratana, Nadia; Gallina, Guglielmo; Panzeri, Valentina; Frangi, Alessandra; Canobbio, Andrea; Reiner, Giorgio
An innovative technology (Physiomimic Technology) has been applied to amino acids (AAs) formulated for patients with phenylketonuria, with the objective of masking AA taste and odor and prolonging AA release in the gut, allowing a physiological absorption. This technology entails that the AAs are processed with functional additives that are able to modify their release and their organoleptic features. Two prototypes, obtained using sodium alginate + ethylcellulose (engP-1) or sodium alginate + ethylcellulose + glyceryl dibehenate (engP-2), have been tested for AA prolonged release versus the same AAs (n-engP) without the application of the Physiomimic Technology. In vitro tests indicated that the technology is able to prolong the release of the engineered AAs versus the free compounds. A crossover in vivo kinetic study in pigs showed reduced peak concentrations (Cmax ) and, as expected, similar areas under the concentration/time curve (up to 5 hours) for the engineered products versus the free AAs. Significantly lower Cmax values ( P < .01) were attained for essential AAs, large neutral AAs, and branched-chain AAs, indicating that the technology is able to reduce the typical absorption peak of free AAs. Taste and odor masking has been obtained as a consequence of the AA coating. The Physiomimic Technology, applied to free AAs, provided AA mixes with improved organoleptic features and with modified AA kinetics sustaining a more physiological AA absorption.